Comparison of patient satisfaction measures between in-person and telemedicine postoperative appointments following third molar surgery. Issue 6 (June 2021) - Champion, A.; Congiusta, A.; Yagnik, A.
Abstract: The goal of this study was to compare key aspects of patient satisfaction in patients who underwent in-person and telemedicine postoperative appointments following third molar surgery. A total of 69 patients undergoing the removal of third molars were randomized to receive their postoperative care either in person or via telemedicine appointments. Following the postoperative visit, patients were asked to complete a survey that assessed elements of patient satisfaction using a visual analog scale. Forty-seven patients (37 female, 10 male) completed the study (in-person n = 24, telemedicine n = 23). The mean total patient satisfaction score (maximum 50) was 46.46 for the in-person group and 48.78 for the telemedicine group; the difference was not statistically significant ( P = 0.11). There were no statistically significant differences in patient satisfaction scores between the two groups with regards to the ease of scheduling the appointment, ease of attending the appointment, perceived usefulness of the appointment, or the quality of patient education received at the appointment. However, the perceived cost-effectiveness was higher for patients in the telemedicine group ( P = 0.01). The results of this study suggest that for third molar extraction surgery, telemedicine and in-office postoperative visits produce similar patient satisfaction experiences, but patient perceived cost-effectiveness was greater for telemedicine visits.